Quality of life of patients with schizophrenia and its determinants - Smitha Ramadas; Vyjayanthi Bonanthaya (Telangana Journal of Psychiatry, 2017)
Introduction: As mortality rates are decreasing, thanks to new inventions and discoveries, morbidity rates are probably on the rise. Schizophrenia is a chronic mental disorder mostly requiring lifelong maintenance treatment. Therefore Quality of life (QOL) is assuming more importance in the medical field as an important outcome measure. Aims: This study was conducted to examine the QOL of patients with schizophrenia and its determinants. Materials & Methods: Quality of life in patients with schizophrenia, aged 18-60 years, with no significant medical and other primary psychiatric illnesses, from the outpatient and inpatient facility of a tertiary care hospital in South India and its association with social and clinical variables was studied. WHO QOL BREF scale was used to assess the QOL. Results & Conclusion: Thirty subjects were recruited for the study. Majority of them were male, single, of rural background and Hindu religion, unemployed with less than 10 years of education. The mean age of patients was 34 years and the mean duration of illness was seven years. QOL improved with age, especially in the physical domain. QOL was significantly poor in professionals, in the environmental domain of QOL scale. In the psychological domain also professionals had poor QOL, though not statistically significant. Depression and general psychopathology item in the PANSS were found to have significant inverse correlation with QOL.